The process of teaching and learning in classes with visual deficient students: perceptions of teachers - Iohanna Elizabeth Beckers; Josefa Lídia Costa Pereira; Anderson Giovani Trogello (Universidade Federal de Santa Maria (UFSM), 2014)
The teaching of astronomy focused on students with special educational needs must happen in order to involve the participant so inclusive in the process of teaching and learning. Thus, students with visual deficient require actions that favor the different senses but sight. Thus, this study set out to interview teachers in early grades of elementary school, aiming to analyze how the process of teaching and learning of astronomical content in classrooms that have included visual deficient students happens. Such analysis showed that the teaching of astronomy practiced by teachers favored an audio-visual language. It may discourage the participation of the visual deficient ones.